Microwave‐Assisted Hydrothermal Synthesis, Crystal Structure, and Thermal Decomposition of Strontium Citrate Monohydrate Sr3(C6H5O7)2·H2O. Issue 4 (18th June 2020) - Hämmer, Matthias; Wessels, Vivien; Ettlinger, Romy; Höppe, Henning. A.
Abstract : Microcrystalline strontium citrate monohydrate Sr3 (C6 H5 O7 )2 · H2 O was prepared by a microwave‐assisted hydrothermal synthesis. Single‐crystal X‐ray structure determination ( P 1, a = 10.0572(4), b = 10.1506(5), c = 10.8531(5) Å, α = 89.642(2)°, β = 67.156(2)°, γ = 62.367(2)°, 3040 independent reflections, 353 refined parameters, wR 2 = 0.066) revealed three different Sr sites coordinated eight‐, nine and ten‐fold by two crystallographically different citrate molecules with one comprising oriental disorder, but not by the crystal water molecule. These findings are supported by energy dispersive X‐ray spectroscopy, powder XRD, infrared spectroscopy and thermal analysis. Further, the latter three methods are applied to the hitherto only strontium citrate hydrate with known crystal structure Sr3 (C6 H5 O7 )2 · 5H2 O and both compounds are compared, especially with respect to their possible application as precursors. Abstract :